The Tarantula Venom Peptide Eo1a Binds to the Domain II S3-S4 Extracellular Loop of Voltage-Gated Sodium Channel NaV1.8 to Enhance Activation - Deuis, Jennifer R.; Ragnarsson, Lotten; Robinson, Samuel D.; Dekan, Zoltan; Chan, Lerena; Jin, Ai-Hua; Tran, Poanna; McMahon, Kirsten L.; Li, Shengnan; Wood, John N.; Cox, James J.; King, Glenn F.; et al. (Frontiers in Pharmacology, 2022)
Venoms from cone snails and arachnids are a rich source of peptide modulators of voltage-gated sodium (Nav) channels, however relatively few venom-derived peptides with activity at the mammalian Nav1.8 subtype have been isolated. Here, we describe the discovery and functional characterisation of beta-theraphotoxin-Eo1a, a peptide from the venom of the Tanzanian black & olive baboon tarantula Encyocratella olivacea that modulates Nav1.8. Eo1a is a 37-residue peptide that increases Nav1.8 peak current (EC50 894 +/- 146 nM) and causes a large hyperpolarising shift in both the voltage-dependence of activation (delta V50 −20.5 +/- 1.2 mV) and steady-state fast inactivation (delta V50 −15.5 +/- 1.8 mV). At a concentration of 10 microM, Eo1a has varying effects on the peak current and channel gating of Nav1.1–Nav1.7, although its activity is most pronounced at Nav1.8. Investigations into the binding site of Eo1a using Nav1.7/Nav1.8 chimeras revealed a critical contribution of the DII S3-S4 extracellular loop of Nav1.8 to toxin activity. Results from this work may form the basis for future studies that lead to the rational design of spider venom-derived peptides with improved potency and selectivity at Nav1.8.